Aplikasi Pengenalan Seni Kerajinan Tangan Masyarakat Dayak Provinsi Kalimantan Tengah Berbasis Android - Haris, Ferdiyani; Ningsih, Tri Kurnia (STMIK Palangkaraya, 2017)
Smartphone has an important role in the world of information. This is because some smartphone already have more functions and capabilities beyond basic capabilities. The most popular smartphone today is A smartphone with Android-based information systems. Utilization of smartphone as A companion in carrying out daily activities is very often used is fundamental in the making recognitions Application Of Handicrafts Dayak's People in Central Borneo Province Based on Android. The problem of this research is how to design and create recognitions Application Of Handicrafts Dayak's People in Central Borneo Province Based on Android that can help users to provide ease in the knowledge of handicrafts from Central borneo. So it can be know later by the public, not only the locals people but people outside the region. The method used in this research include observation, interviews, literature and documentation. Software development method that used for creation flow system using methods developed software system development life cycle ( SDLC ) with the waterfall model development approach. Software used in the manufacture of recognitions Application Of Handicrafts Dayak's People in Central Borneo Province is A version of the Eclipse ADT Mars.2.